Prognostic significance of Wilms’ tumor gene 1 expression in children with B-cell precursor acute lymphoblastic leukemia - Xue, Yu-juan; Wang, Yu; Zhang, Le-ping; Lu, Ai-dong; Jia, Yue-ping; Zuo, Ying-xi; Zeng, Hui-min (Frontiers in Oncology, 2024)
The prognostic role of Wilms' tumor 1 (WT1) gene expression at diagnosis in children with B cell precursor acute lymphoblastic leukemia (BCP-ALL) is still controversial. We detected the WT1 transcript levels of 533 de-novo pediatric BCP-ALL patients using TaqMan-based real time quantitative PCR (RQ-PCR), and analysed their clinical features. The WT1 transcript levels differed amongst the distinct molecularly defined groups, with the highest levels in the KMT2A rearrangements (KMT2A-r) group. According to results of the X-tile software, all the patients were divided into two groups: WT1/ABL ≥ 0.24% (group A) and < 0.24% (group B). The proportions of patients who had an age ≥ 10 years old, immunophenotype of Pro-B, be in high-risk group, or with minimal residual disease (MRD) ≥ 0.01% at week 12, were significantly higher in group A than in group B. In the B-other group, WT1 overexpression was an independent risk factor of overall survival (OS) rate (P = 0.042), and higher MRD ≥ 0.01% at week 12 was associated with lower OS (P＜0.001) and event free survival (EFS) rate (P＜0.001). Moreover, subgroup analysis revealed that in patients with initial WBC ＜ 50×10 9 /L, or MRD ＜ 0.1% at day 33, or MRD ＜ 0.01% at week 12, or in the standard-risk group, WT1 overexpression led to a poorer outcome in comparison with those with WT1 downexpression (P＜0.05). Therefore, pediatric BCP-ALL with WT1 overexpression had unique clinico-pathological characteristics and poor treatment response.In B-other patients, WT1 overexpression at diagnosis predicted an inferior prognosis. The WT1 gene may serve as a biomarker for monitoring residual disease in the B-other population, especially in children in the SR group.